Implementing international environmental law and policy : an interactive approach to environmental regulation - Smallwood, Joanna Miller (Routledge research in international environmental law, 2024)
"This book introduces a novel discourse, based on socio-legal theory of compliance with international environmental law, which addresses the overarching question: when can international environmental law and policy achieve implementation, compliance and be effective? Offering an important contribution to academic and practical understandings of implementation and compliance with international environmental obligations, the book firstly critiques existing multidisciplinary theories of law and then brings together international and domestic legal theories to highlight their symbiotic relationship. It also stresses the importance of interactions between domestic and international legal and policy processes. This pioneering discourse is argued to be transformative to international environmental regimes and offers a way for them to be truly normative and to achieve compliance. The book will be of interest to students and scholars in the field of socio-legal studies and international environmental law and policy"--